2022
DOI: 10.1080/22221751.2022.2072773
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of homologous and heterologous BNT162b2, CoronaVac, and AZD1222 booster vaccination against Delta and Omicron SARS-CoV-2 infection

Abstract: Given emerging evidence of immune escape in the SARS-CoV-2 Omicron viral variant, and its dominance, effectiveness of heterologous and homologous boosting schedules commonly used in low-to-middle income countries needs to be re-evaluated. We conducted a test-negative design using consolidated national administrative data in Malaysia to compare the effectiveness of homologous and heterologous BNT162b2, CoronaVac, and AZD1222 booster vaccination against SARS-CoV-2 infection in predominant-Delta and predominant-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 13 publications
7
42
3
Order By: Relevance
“…Thus, inactivated vaccines do induce a rise in nucleocapsid antibodies [ 35 ] and prevents its use in the diagnosis of asymptomatic/pauci-symptomatic post-vaccination infection as well as the identification of previous exposure to COVID-19. The nucleocapsid antibodies developed in response to inactivated vaccines may have a theoretical benefit against the Omicron strain; however, real-world evidence [ 36 ] has shown that mRNA vaccines, even when used in a heterologous dosing regimen, provided greater protection against COVID-19 infection during waves of Omicron predominance. Although we were able to assess S-Ab and N-Ab responses to vaccines, we were unable to assess the development of memory B cells in response to inactivated vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inactivated vaccines do induce a rise in nucleocapsid antibodies [ 35 ] and prevents its use in the diagnosis of asymptomatic/pauci-symptomatic post-vaccination infection as well as the identification of previous exposure to COVID-19. The nucleocapsid antibodies developed in response to inactivated vaccines may have a theoretical benefit against the Omicron strain; however, real-world evidence [ 36 ] has shown that mRNA vaccines, even when used in a heterologous dosing regimen, provided greater protection against COVID-19 infection during waves of Omicron predominance. Although we were able to assess S-Ab and N-Ab responses to vaccines, we were unable to assess the development of memory B cells in response to inactivated vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Western countries, the population in Shanghai was mostly vaccinated with domestically-developed inactivated vaccines, which had relatively lower effectiveness in preventing SARS-CoV-2 infections due to their lower antibody-neutralizing responses compared to mRNA vaccines. 9 , 10 In addition, the vaccination coverage was highest in the young population (100.0% in individuals aged between 12 and 17 years had completed the primary vaccine schedule as of March 2022) 11 and lowest in the elderly (only 62.0% in individuals aged 60 years or older had completed the primary schedule as of April 2022). 12 Most importantly, a wide range of NPIs were adopted to achieve outbreak containment, in contrast to the mitigation strategy adopted by most regions outside mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…Shanghai is one of the most populous and economically advanced metropolises in China, with a population of nearly 25 million 8 and unique features compared to other areas in mainland China and abroad. The population in Shanghai was mostly vaccinated with domestically-developed inactivated vaccines, which had relatively lower effectiveness in preventing SARS-CoV-2 infections due to their lower antibody-neutralizing responses compared to mRNA vaccines 9,10 . In addition, the vaccination coverage was highest in the young population (100.0% in individuals aged between 12 and 17 years had completed the primary vaccine schedule as of March 2022) 11 and lowest in the elderly (only 62.0% in individuals aged 60 years or older had completed the primary schedule as of April 2022).…”
Section: Introductionmentioning
confidence: 99%